101 techniques acrylics - Sanmiguel, David (Hauppage, NY Barron's Educational Series, Inc., 2014)
Presents color illustrations, instructions, and difficulty levels in order to practice different techniques used for acrylic paintings.
Original Spanish Title: 101 técnicas acrlico.
Keywords: Acrylic painting -- Technique